PENGARUH E-WOM, QUALITY PRODUCT DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUCT SOMETHINC - Adila ramadhani; Meylani Tuti (Panorama Nusantara, 2024)
This research aims to determine the influence of EWOM, Brand Image, Product Quality on purchasing decisions. The population in this study were somethinc skincare users. The sampling technique used was accidental sampling with a total of 161 respondents. The data analysis method uses a structural equation model with the help of smartPLS software. The research results show that there is a significant influence of EWOM and Product Quality on purchasing decisions. Meanwhile, the results also show that there is no influence of Brand Image on purchasing decisions.